Relief for an unquiet mind: Improving outdoor environments for long-term mental health facilities using user-centered design - Quincke, Madison L. (Kansas State University, 2020)
Outdoor environments can greatly contribute to the ways people heal, reduce stress, clear their head, and feel integrated or accepted into the environment in which they live. Despite this scientific evidence, in most cases, not enough outdoor spaces are provided to the patients and staff of mental health facilities. Existing therapeutic landscape design guidelines lack specificity related to severe and persistent mental health (SPMI) conditions and spaces for therapy treatments. This study aims to use two environmental psychology frameworks (therapeutic landscape guidelines and the Reasonable Person Model) to begin to develop a set of informed guidelines that can be used to design more supportive outdoor therapeutic environments for staff in mental health facilities. To achieve this goal, the study investigated three mental health hospitals in Kansas through two methods: site inventory and analysis and online/ paper photo surveys. The surveys were based on the literature on therapeutic landscapes and restorative environments as well as mental health symptoms to identify which guidelines are specific to mental health and which are generally applicable to all healing spaces. The final objective is to discover the environmental needs and preference of mental healthcare setting users. Findings from the site analysis and surveys were applied to a projective design at one of the three study sites- Osawatomie State Hospital. 140 responses from staff and 14 responses from patients were collected through the survey. Because there were not enough patient surveys collected to be statistically reliable, only the data collected from the staff was used in the projective design. Overall, by linking psychology principles and landscape architecture, this study aims to take a step toward developing a set of evidence-based planning and design guidelines to create supportive outdoor spaces that better meet the needs of the patients and staff of mental health hospitals, aiding in the therapeutic process for the staff over time.
Keywords: Landscape Architecture; Healthcare Design; Mental Illness; Reasonable Person Model; Restorative Environments